1985
DOI: 10.1029/ja090ia07p06379
|View full text |Cite
|
Sign up to set email alerts
|

Refilling of geosynchronous flux tubes as observed at the equator by GEOS 2

Abstract: During periods of extended quiet geomagnetic activity the geosynchronous satellite orbit lies inside the plasmasphere. Five such periods were observed by the GEOS 2 satellite. During the initial 48 hours of such periods the equatorial plasma flux tube density increases at 30 to 50 cm−3/day. However, on reaching ∼100 cm−3 the refilling rate decreases, and refilling is limited. Only when the density reaches ∼100 cm−3 do the plasma characteristics and fluctuations appear to be plasmaspheric and the flow predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…However, we intend to explore the impact of E×B motion on plasmasphere refilling with the self-consistent SAMI3/RCM (Rice Convection Model) code (Huba et al, 2005) in the near future. With the coupled model, future work will include (a) magnetospheric convection, which may limit saturation densities at these L-shells, (b) co-rotation, which would be necessary for accurate simulations at geosynchronous orbit and for comparisons to the relative wealth of data from that altitude (Sojka and Wrenn, 1985;Song et al, 1988;Singh and Horwitz, 1992;Su et al, 2001, and references therein), (c) consideration of the dependence of refilling on magnetospheric activity (see, e.g. Song et al, 1988), and/or (d) independent variations in the daily and average F 10.7 indices, so as to partially distinguish thermospheric heating effects from photo-ionization effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we intend to explore the impact of E×B motion on plasmasphere refilling with the self-consistent SAMI3/RCM (Rice Convection Model) code (Huba et al, 2005) in the near future. With the coupled model, future work will include (a) magnetospheric convection, which may limit saturation densities at these L-shells, (b) co-rotation, which would be necessary for accurate simulations at geosynchronous orbit and for comparisons to the relative wealth of data from that altitude (Sojka and Wrenn, 1985;Song et al, 1988;Singh and Horwitz, 1992;Su et al, 2001, and references therein), (c) consideration of the dependence of refilling on magnetospheric activity (see, e.g. Song et al, 1988), and/or (d) independent variations in the daily and average F 10.7 indices, so as to partially distinguish thermospheric heating effects from photo-ionization effects.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, both the data (Park, 1970;Sojka and Wrenn, 1985;Song et al, 1988;Singh and Horwitz, 1992;Lawrence et al, 1999;Su et al, 2001;Tu et al, 2003) and the models show that for a given flux tube, refilling begins with high-speed upflows from the two conjugate ionospheric sources, followed by a process in which the plasma is trapped or thermalized and, lastly, by a fluid-like evolution over a number of days. In general, early stage refilling (inflow and trapping; t<24 h) proceeds at a lower rate than late stage refilling (>24 h) (Lawrence et al, 1999).…”
Section: Early and Late Stage Refillingmentioning
confidence: 99%
“…The appearance of the bulge in the evening sector is taken to be a sign of modest geomagnetic activity. When geomagnetic activity is very low for a few days, cool, dense plasmaspheric material is encountered over nearly all of geosynchronous orbit [e.g., $ojka and Wrenn, 1985]. This buildup of material in the outer plasmasphere is believed to be caused by cold outflows from the ionosphere into magnetic flux tubes that are on drift trajectories that do not encounter the magnetopause (see section 8).…”
Section: Plasmaspheric Dynamics Through the CX Storm •mentioning
confidence: 99%
“…In this study, Gallagher et al used GEOS-2 total electron density data from Higel and Wu [1984] to derive an early time refilling rate of 0.56 cm -3 h -•. Earlier studies conducted by Sojka and Wrenn [1985], using cold ion data from the GEOS-2 satellite, and Song et al [1988], using the relaxation sounder also on the GEOS-2 satellite, addressed late time plasmasphere refilling, or the refilling that takes place over the course of 2-4 days during periods of low geomagnetic activity. In particular, the study by Sojka and Wrenn identified two periods of low geomagnetic activity where they observed plasmasphere refilling.…”
Section: Paper Number 1998ja900087mentioning
confidence: 99%
“…In addition, Plates 1 b and 1 e show that the cold ion azimuthal distribution changed from northward field-aligned to isotropic as the density increased. This transition to isotropy has been observed before at geosynchronous orbit [cf., Sojka and Wrenn, 1985], with the interpretation that an isotropic distribution signifies an entrance into the filling plasmasphere. The data in Plate 1 therefore show that the MPA instruments are able to measure both early and late time plasmasphere refilling.…”
Section: Measurements Of Geosynchronous Cold Ion Density Using the Mpmentioning
confidence: 99%